Pazopanib as a possible option for the treatment of metastatic non-clear cell renal carcinoma patients: a systematic review - Melissa Bersanelli; Matteo Brunelli; Letizia Gnetti; Umberto Maestroni; Sebastiano Buti (Therapeutic Advances in Medical Oncology, 2020)
Background: Effective systemic treatment of non-clear cell renal carcinoma (nccRCC) is still an unmet clinical need, with few studies to support an evidence-based approach. To date, the only recommended standard first-line treatment is sunitinib. Pazopanib may also be used in nccRCC but its place in therapy is not clearly established. It has comparable efficacy and better tolerability than sunitinib in clear cell renal carcinoma. Our objective was to review the use of pazopanib in metastatic nccRCC. Methods: We conducted a systematic review according to PRISMA guidelines. Any type of study reporting the use of pazopanib in metastatic renal cell carcinoma including cases with non-clear cell histology was eligible. Results: In all, 15 studies were included in our analysis, including a total of 318 nccRCC patients treated with pazopanib. Most studies were retrospective ( n  = 12); three were prospective trials. The specific outcomes of nccRCC patients were reported by four studies. Pazopanib alone as first-line treatment gave overall response rates ranging from 27% to 33%, disease control rates of 81–89%, median progression free survival of 8.1–16.5 months and median overall survival of 17.3–31.0 months. Grade 3–4 adverse events rates were 21–55%. Conclusion: The present review provides for the first time a systematic summary of evidence about the possible use of pazopanib as first-line treatment for nccRCC, with a favorable outcome despite the low strength of evidence. Pazopanib could be considered as a possible therapeutic option in this setting.